Life cycle assessment of a high-tech vertical decoupled aquaponic system for sustainable greenhouse production - Ravani, Maria; Chatzigeorgiou, Ioanna; Monokrousos, Nikolaos; Giantsis, Ioannis A.; Ntinas, Georgios K. (Frontiers in Sustainability, 2024)
Aquaponics provide multiple benefits due to the simultaneous yield of vegetables and fish, however they are characterized by increased greenhouse gas emissions owing to intensive production system. The most appropriate method for quantifying the environmental effects of these systems is Life Cycle Assessment with which the identification of hotspots and the suggestion of improved production plans can be achieved. The purpose of the present study was to evaluate the environmental impact of a pilot high-tech aquaponic system utilized for the simultaneous production of baby lettuce and rocket as well as rainbow trout, in indicators such as Global Warming Potential. To achieve this goal, data on inputs and outputs were collected from 12 case studies that were implemented, combining different fertilizer treatments, substrate choices, plant species cultivated and water source provision. Life Cycle Assessment was performed using SimaPro v.9.4.0.2 software. The results showcase that the optimal case studies include the cultivation of baby lettuce and rocket in perlite substrate using wastewater from fish and partial use of synthetic fertilizers. Indicatively, Global Warming Potential of these cases was calculated at 21.18 and 40.59 kg CO2-eq/kg of vegetable respectively. The parameter with the greatest impact on most of the environmental indicators was electricity consumption for the operation of the oxygen supply pump for the fish tanks, while greenhouse infrastructure had the greatest impact in Abiotic Depletion and Human Toxicity impact categories. In an alternative production scenario tested where renewable energy sources were used, system impacts were reduced by up to 50% for Global Warming Potential and 86% for Eutrophication impact. The results of this study aspire to constitute a significant milestone in environmental impact assessments of aquaponic production systems and the adoption of more sustainable farming practices.